Підбір умов для введення в культуру in vitro рослин Lycium barbarum (L.) - Жук, В.П.; Забейда, О.Ф.; Науменко, В.Д. (Фактори експериментальної еволюції організмів, 2015)
Aims. Chinese wolfberry or goji (Lycium barbarum (L.)) is attractive object for plant biotechnologists due to the high content
of such biologically active compounds as polysaccharides, carotenoids and flavonoids. Methods. Our study was aimed to
select the optimal conditions for the initiation of L. barbarum aseptic callus in vitro culture using leaf disks and internodes as
explants. Results. In the present study, the best explants and corresponding treatment for callus induction were determined.
The optimized protocol includes 25 g of sucrose per 1L of Murashige-Skoog medium. In turn, optimal phytohormone
concentrations for the intensive growth of callus were 0.1 mg/L 2,4-D for internodes and 0.2 mg/L 2,4-D for leaf discs, while
NАА and kinetin were not such effective. Conclusions. Our optimized protocol for L. barbarum callus initiation could be
used for further studies of the synthesis and accumulation of biologically active metabolites in goji tissue culture.
Keywords: Lycium barbarum (L.), callus, in vitro culture, 2,4-D.